Batch filtration model of proanthocyanidins purification process from sorghum pericarp extract using polyethersulfone membrane - Afandy, Moh. Azhar; Sediawan, Wahyudi Budi; Hidayat, Muslikhin; Susanti, Devi Yuni; Sawali, Fikrah Dian Indrawati; Mustikaningrum, Mega (Jurnal Rekayasa Proses, 2024)
Sorghum is one type of plant rich in polyphenol chemicals, one of which is proanthocyanidin. The goal of this work was to construct a filtration equation model for the purification of proanthocyanidin compounds in sorghum pericarp extracts utilizing ultrafiltration methods at varied transmembrane pressures and molecular weight cut-off values on asymmetric polyethersulfone (PES) membranes. The pressure difference and size of MWCO were used to determine the rate of cake formation induced by fouling and concentration polarization. The model suggested in this work is based on a compressible filtration model that can represent the decrease in permeability values and the cake formation process produced by the compression of particles deposited on the surface of the membrane. The results reveal that the transmembrane pressure and MWCO considerably affect the performance of the proanthocyanidins separation process employing ultrafiltration membrane technology. The higher the transmembrane pressure, the higher the permeation flow rate. The effect of MWCO on permeability varies with the type of membrane and fluid employed. The larger the MWCO, the higher the permeability since the membrane pores are more significant and more accessible for the liquid to pass through. The high transmembrane pressure not only helps the feed flow swiftly through the membrane and overcomes the resistance but also encourages substance accumulation until the bulge component drops, resulting in a blocking mechanism in the surface or pore of the membrane. The batch filtration model suggested in this work exhibits a reasonably good fit, which can be seen from the projected data values using a model that tends to approach the experimental data values and may be employed as a model that depicts the cake-forming process on the membrane surface.